The complementarity of feed resources for animal production in Africa - Stares, J.E.S.; Said, A.N.; Kategile, J.K. (International Livestock Centre for Africa, 1992)
These are the Proceedings of the last joint workshop of the Pasture Network for Eastern and Southern Africa (PANESA) and the African Research Network for Agricultural Byproducts (ARNAB), held in Gaborone, Botswana, 4-8 March 1991. This volume contains the three addresses delivered at the opening session together with 38 full texts and 12 abstracts of papers presented at the workshop. The scientific papers are grouped in three sections, corresponding to the main themes of the workshop. Thus 13 papers and five abstracts address various aspects of the use of forage legumes in animal nutrition and the nutritive value of planted and natural pastures; 18 papers and five abstracts deal with animal production systems based on crop residues and forage legumes; and nine papers and two abstracts are concerned with institutional and policy issues that affect integration of feed resource use on-farm.